KEADAAN GIZI ANAK BALITA DI DAERAH UPGK YANG BAIK: Studi Kasus di Tujuh Desa di Lima Provinsi - Herman Sudiman (Persagi, 1987)
KEADAAN GIZI ANAK BALITA DI DAERAH UPGK YANG BAIK: Studi Kasus di Tujuh Desa di Lima Provinsi